Perception of Early Male Adolescents Living in the Indonesian Red-Light District - Hidayat, Muhamad Taufik; Mokhtari, Rafidah Hanim Binti; Rosyidah, Hanifatur (International Journal of Psychosocial Rehabilitation, 2020)
The red-light district of Argorejo, Semarang City is the biggest                                                                                                                prostitution area in Indonesia. In 2015, there were more than 500 early male adolescents lived in the area. This study captured the profile of the early male adolescents living in the surrounding area of the red-light district of Argorejo and their perception of the practice of prostitution. The authors used a qualitative research method with a descriptive phenomenology approach. The main informants consisted of four early male adolescents with predetermined criteria. Meanwhile the supporting informants consisted of the main informants' neighbors, a local leader, and an activist of a local non-government organization. The data collection used an in-depth interview. The data obtained were analyzed by Interpretative Phenomenological Analysis. There is no significant difference compared to early male adolescents in Semarang City or Indonesia in general. They hope the government will immediately close the red-light district of Argorejo as soon as possible.